The founding of Israeli democracy, 1948-1967 - Medding, Peter (Oxford University Press, 1990)
Of the twenty-one countries which established democratic states after 1945, only Israel has remained a functioning democracy, despite the adverse conditions under which it was founded. In this study of Israel's founding years from 1948 to 1967, Peter Medding, a highly regarded scholar of Jewish society and politics, asks why this was the case. He provides a lucid account of the political and historical background to this distinctive period, the political relations which characterized it, and the changes in the balance of forces which brought it to an end. He describes the state-building process and the role played by David Ben-Gurion and other politicians in moving from consensus politics to a majoritarian democracy. Medding's analysis is further enriched by his comparisons of the development of Israeli democracy with that of other countries.